IN VITRO DIRECT ORGANOGENESIS AND PLANTLET FORMATION FROM DE EMBRYONATED COTYLEDON EXPLANTS OF PEANUT (ARACHIS HYPOGAEA L.) - RAJINIKANTH MARKA,; MOHAMMAD HADI EBRAHIMZADEH,; ARCHANA KURRA,; ARCHANA PAMULAPARTHI,; RAMA SWAMY NANNA, (International Journal of Pharma and Bio Sciences, 2014)
Peanut/Groundnut (Arachis hypogaea L.) is economically the most important species of the Legume family. It is cultivated for its oil and proteins. The present study reports on the direct induction of multiple shoots from de-embryonated cotyledon explants of peanut cvs ICG 7827 and ICG 13942 which is prerequisite for genetic transformation experiments. Longitudinally halved cotyledons were inoculated on shoot induction medium (SIM) containing MS salts with B5 vitamins supplemented with different concentrations and combination of plant growth regulators (BAP/TDZ, NAA/IAA+BAP/TDZ). Maximum number of direct multiple shoots/explant (45.67±0.23) with 94% of shoot conversion was found at 0.5 mg/L IAA+15 mg/L TDZ in cv ICG 13942 followed by 37.82±0.11 multiple shoots/explant with 85% of conversion at 0.5 mg/L NAA+20 mg/L BAP in cv ICG 7827. The individual shoots were elongated on shoot elongation medium (SEM) fortified with 0.5 mg/L BAP. For in vitro rooting, these elongated micro-shoots were transferred on to root induction medium (RIM) supplemented with 1 mg/l NAA. In vitro rooted plantlets were transferred to soil: sand: vermicompost (1:1:1) mixture and subsequently these were acclimatized in the green house. Thus, the regeneration protocol developed in the present investigation can be used for Agrobacterium mediated genetic transformation to transfer fungal resistant genes.